FOSTERING ORGANIZATIONAL CITIZENSHIP BEHAVIOR AMONG CIVIL SERVANT: THE ROLES OF GREEN HUMAN RESOURCES MANAGEMENT, ORGANIZATIONAL COMMITMENT, AND PERCEIVED ORGANIZATIONAL SUPPORT - Siti Waliah; Reina A. Hadikusumo; Acai Sudirman (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
This paper aims to investigate the impact of the GHRM, organizational commitment and perceived organizational support on organizational citizenship behavior among public servants in the Province of South Sumatra, Indonesia. A quantitative study using cross-sectional surveys was conducted with a sample of 250 public servants selected through purposive sampling. The partial least squares structural equation modeling (PLS-SEM) method was used to examine the data structure and a set of meaningful hypotheses, including: Measurement models, Structural models (fit), GHRM has influence and positive significance to OCB, organizational commitment has influence and positive significance to OCB, and perceived organizational support has influence and positive significance to OCB. The research found that GHRM, organizational commitment, and perceived organizational support positively and significantly influence OCB, and that GHRM has the strongest effect on OCB. Also, this research contributes towards Social Exchange Theory, and Organizational Support Theory on the concept of OCB by offering an integrated explanation of OCB's antecedents in the public sector domain. From practical perspective, the result supports managerial insight to develop the human resource strategies in creating a well supportive organizational culture and environment towards the creation of civil servants’ citizenship behaviour, thus increase organizational performance and sustainability